Prosumer‐centric energy storage system and high voltage distribution network topology Co‐optimisation for urban grid congestion management. Issue 4 (29th March 2022) - Zhang, Xi; Liu, Youbo; Zeng, Yu; Wu, Gang; Liu, Junyong
Abstract: The surge of electricity load and the growing number of renewable energy sources (RESs) in urban power grid result in severe and frequent congestion for transmission networks. This causes the transmission system operators (TSOs) perform the high voltage distribution network (HVDN) reconfiguration frequently. The frequent reconfiguration of the HVDN will cause the fast degradation of high voltage circuit breakers, high maintenance and operational cost, and stability problems. To reduce the frequency of HVDN reconfiguration, this paper proposes a prosumer‐centric energy storage system (ESS) and HVDN topology co‐optimisation for transmission congestion management. Numerical results show that with the assist of ESS operational strategy, the reconfiguration frequency of HVDN can be significantly reduced while mitigating the transmission congestion.